2016
DOI: 10.1063/1.4965447
|View full text |Cite
|
Sign up to set email alerts
|

How do liquid fuel physical properties affect liquid jet development in atomisers?

Abstract: The influence of liquid fuel properties on atomisation remains an open question. The droplet sizes in sprays from atomisers operated with different fuels may be modified despite the small changes of the liquid properties. This paper examines experimentally the development of a liquid jet injected from a plain orifice in order to evaluate changes in its behaviour due to modifications of the liquid properties, which may influence the final atomisation characteristics. Two aviation kerosenes with similar, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
6
17
1
Order By: Relevance
“…The present work is in line with several contemporary efforts to assess the influence of composition and physical properties on the atomization characteristics of alternative fuels [19][20][21][22][23]. The work was part of a larger effort to investigate the applicability of fuels that can be processed to look like kerosene, as practical alternatives to fossil fuels by the Virtual Fuel Centre of the Environmentally Compatible Air Transport System project (ECATS) [24][25][26].…”
Section: Introductionsupporting
confidence: 53%
“…The present work is in line with several contemporary efforts to assess the influence of composition and physical properties on the atomization characteristics of alternative fuels [19][20][21][22][23]. The work was part of a larger effort to investigate the applicability of fuels that can be processed to look like kerosene, as practical alternatives to fossil fuels by the Virtual Fuel Centre of the Environmentally Compatible Air Transport System project (ECATS) [24][25][26].…”
Section: Introductionsupporting
confidence: 53%
“…The results of spray tip penetration and spray area of biodiesel blends and diesel showed that higher injection pressure result in a longer spray tip penetration and larger spray area than that at lower injection pressures at same elapsed time after the start of injection. Even small changes in the physical properties of the fuels are known to modify the interfacial velocities and consequently the internal injected jets velocity profiles [9]. Furthermore, the use of biodiesel blends in modern engines interferes in a complex way with the fuel injectors, since the injection orifices in the nozzles are created by electro-erosion machining, (electrical discharge machining, EDM) to produce diameters of the order of 100 µm, with their leading edges rounded off by hydro-erosion machining [10].…”
Section: Introductionmentioning
confidence: 99%
“…1). It should be noted that, as the last term in (15) indicates, expressions (14)- (16) are for the components of velocity in the observer's reference frame so that, to obtain the corresponding components in the coordinate frame rotating with the disk, the last term on the right-hand side of (15) should be taken out. Thus, to find the dominating wave solution for a given wave frequencyω, one needs, first, to calculate the characteristic film thickness H from (5) and the local values of the similarity parameters δ and E from (6) and (7).…”
Section: A Film Regionmentioning
confidence: 99%
“…Once the dominating wave is found, one can use the film thicknessh obtained as part of the solution and the velocity profile (14)- (16) as the inlet conditions at S 1 . As already mentioned, in (14)-(16), we drop the last term on the right-hand side of (15) to have the azimuthal velocity component in the rotating frame.…”
Section: A Film Regionmentioning
confidence: 99%
See 1 more Smart Citation